Effects of garlic supplementation on the growth performance rate in climbing perch (Anabas testudineus) diet - Pengseesang, R.; Wiangsamut, B.; Kulabtong, S. (International Journal of Agricultural Technology, 2024)
The study of garlic supplementation on the growth of Anabas testudineus or climbing perch resulted to the final weight of length gain (LG), weight Gain (WG), percentage weight gain, (PWG), averaged diary growth (ADG), specific growth rate (SGR) and survival rate (SR) were significantly differed. Statistically significant (p<0.05) was showed in diet supplemented with 20 g of garlic/1 kg of diet which showed the highest mean, followed by the garlic supplements with 10, 5, and 0 g kg-1 of diet, respectively. All observed values ​​were averaged daily feed intake. (ADFI), Feed conversion ratio (FCR) and feed efficiency (FE) were significantly different (p<0.05). Diet supplemented with 20 g of garlic/1 kg of diet had the best average, followed by namely, 10, 5, and 0 g of garlic supplement/1 kg of diet, respectively. Water temperature, pH and dissolved oxygen (DO) were significantly different (p<0.05). Diets supplemented with garlic 20 g/1 kg of diet had the highest mean, followed by garlic supplements at 10, 5, and 0 g kg-1 of diet, respectively. All observed values ​​were fillet proportion, skeleton proportion, and fish weight/liver weight index (Hepatosomatic index, HSV) were significantly different (p<0.05). Diet supplemented with 20 g of garlic/1 kg of diet showed the best average, followed by garlic supplements with 10, 5, and 0 g kg-1 of diet, respectively. The fish weight index per internal organ weight (Viscerosomatic index, VSI) was not significantly different (p>0.05). Therefore, garlic can be added to fish diet up to 20 g kg-1 of diet, which revealed a beneficial effect on the growth of fish.